Niger : Joint Staff Advisory Note on the Poverty Reduction Strategy Paper. (IMF Staff Country Reports; Country Report ;, 2013)
Niger's new Poverty Reduction Strategy (PDES) represents its overarching reference framework for the government's development agenda. It also proposes changes in policy orientation and institutional arrangements to respond to recent developments in Niger and in the subregion. The PDES was developed in an inclusive participatory process. Overall, it provides a comprehensive analysis of development challenges and a plan to achieve accelerated sustainable growth, identifies key risks to the achievements of the objectives as well as mitigating measures.